Location of P element insertions in the proximal promoter region of Hsp70A is consequential for gene expression and correlated with fecundity in Drosophila melanogaster. - Chen, B.; Shilova, V.Y.; Zatsepina, O.G.; Evgen'ev, M.B.; Feder, M.E. (Cell Stress & Chaperones, 2008)
We compared a series of Drosophila strains with P element insertions from -28 to -144 nucleotides 5' to the transcription start site of the Hsp70A genes-corresponding to the range of naturally occurring P element insertion sites-to elucidate the consequences of insertion site for Hsp70A gene expression. Although all insertions reduced Hsp70A expression below that of a control strain, the magnitude of the reduction was inversely related to the number of nucleotides between the transcription start site and the insertion site. A pre-existing hypothesis is that naturally occurring transposable element insertions in Hsp promoters may be beneficial in some circumstances, which may account for their retention in natural populations. In the present study, in a control line heat shock reduced fecundity, whereas in lines with P element insertions heat shock typically increased fecundity. Finally, according to cluster-specific quantitative RT-PCR, expression of the Hsp70A cluster genes was typically greater than that of the Hsp70B gene cluster genes, although the latter are more numerous and, in this case, free of P element insertions.